Internal Forecasts in Multi‐Location Firms - GALLO, LINDSEY; LABRO, EVA; OMARTIAN, JAMES D. (Journal of Accounting Research, 2026)
ABSTRACT We investigate the dynamics of internal forecasting in multi‐location firms and the relations between forecast characteristics and investment. Using U.S. Census microdata on plant‐level growth expectations, we find that plants within multi‐location firms make forecasts that are both more certain and less accurate than those of standalone plants. We provide evidence suggesting that headquarters infers uncertainty from inter‐plant forecast disagreement, and that headquarters is able to facilitate the use of relevant information held by one plant but applicable to another. Differences between peer and focal plants' forecasts predict forecast errors and relate to investment decisions at the focal plant, suggesting that information from multiple sources is integrated into capital allocation decisions. Headquarters' heavier use of peer plant forecast information when focal plants are more uncertain likely weakens focal plant managers' incentives to consider extreme scenarios when forecasting.